2020
DOI: 10.21203/rs.3.rs-116158/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Randomized Clinical Trial on the Effect of Foot Reflexology in the Fourth Stage of Labor on Uterine After Pain

Abstract: Objective: Uterine after-pains are among the most prevalent complaints after natural vaginal delivery. Non-pharmacological treatment modalities to relieve after-pains are an important care priority. This study aimed to investigate the effect of foot reflexology in the fourth stage of labor on after-pains in multiparous women.Methods: This single-blind randomized clinical trial recruited 80 eligible pregnant women presenting to Allameh Bohlool Hospital in Gonabad and 17-Shahrivar Hospital in Mashhad in 2019. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…The mechanism of acupressure is similar to that of reflexology based on meridians, energy highways of the body [ 52 ]. Wang et al (2014) in China showed an increase in sexual function of the auricular acupressure group 3, 6, and 9 months after the start of the intervention compared with the control group [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of acupressure is similar to that of reflexology based on meridians, energy highways of the body [ 52 ]. Wang et al (2014) in China showed an increase in sexual function of the auricular acupressure group 3, 6, and 9 months after the start of the intervention compared with the control group [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Bahri et al about the effect of F-REFL on postoperative pain and bleeding in the fourth stage of labor revealed that reflexology positively reduces postoperative pain. Labor pain in the fourth stage of labor and pain intensity after the intervention in the intervention group was lower than in the control group, indicating the positive effect of F-REFL on reducing LP (37). The findings of Goweily, which evaluated the effectiveness of reflexology on the pains of the first stage of labor, presented a significant difference in the severity of LP between the intervention group and the control group (38).…”
Section: The Effect Of Foot Reflexology On Labor Painmentioning
confidence: 98%